2020
DOI: 10.3389/fmicb.2020.509525
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Biofilms and Their Response to a Relevant in vivo Iron Source

Abstract: Biofilm infections can be chronic, life threatening and challenging to eradicate. Understanding in vivo stimuli affecting the biofilm cycle is one step toward targeted prevention strategies. Iron restriction by the host is a stimulus for biofilm formation for some Staphylococcus aureus isolates; however, in some infection scenarios bacteria are exposed to abundant amounts of hemoglobin (Hb), which S. aureus is able to use as iron source. Thus, we hypothesized a role for Hb in the biofilm infection. Microplate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Iron was recently found to be associated with biofilm formation, antibiotic susceptibility, and pathogenicity in several bacterial species, although conclusions from multiple studies were highly inconsistent ( 32 , 37 40 ). In S. aureus , iron restriction enhances biofilm formation, and iron sourced from hemoglobin causes thicker and more structured biofilms than inorganic iron does ( 41 , 42 ). Mounting numbers of studies have focused on the antimicrobial activity of various antibiotics that were directly or indirectly linked to iron homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Iron was recently found to be associated with biofilm formation, antibiotic susceptibility, and pathogenicity in several bacterial species, although conclusions from multiple studies were highly inconsistent ( 32 , 37 40 ). In S. aureus , iron restriction enhances biofilm formation, and iron sourced from hemoglobin causes thicker and more structured biofilms than inorganic iron does ( 41 , 42 ). Mounting numbers of studies have focused on the antimicrobial activity of various antibiotics that were directly or indirectly linked to iron homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus Newman has already been used for many studies on biofilm formation (e.g., Johnson et al, 2008 ; Abraham and Jefferson, 2012 ; Forson et al, 2020 ; Inés Molina et al, 2020 ; Pinto et al, 2020 ) although it is not considered a very good biofilm forming strain and the same is true for the ica negative S. epidermidis strain (e.g., Stepanovic et al, 2000 ; Lee et al, 2016 ; Paduszynska et al, 2019 ; Di Pilato et al, 2020 ; Paulitsch-Fuchs et al, 2021 ). However, the variant of the S. aureus strain used in this study S. aureus Newman D2C is considered to be a relatively good biofilm forming strain ( Grundmeier et al, 2004 ; Tsompanidou et al, 2010 ; Abraham and Jefferson, 2012 ; Dauros-Singorenko et al, 2020 ; Paulitsch-Fuchs et al, 2021 ). Abraham and Jefferson (2012) showed that the autolysin activity in the Newman D2C variant was low enough to allow the expression of ClfB on the cell surface, which seems to be (at least partly) responsible for the difference in biofilm forming abilities between the two strains.…”
Section: Discussionmentioning
confidence: 99%
“…and high iron contents did show a negative influence on agr expression in the hemoglobin study byDauros- Singorenko et al (2020), therefore possibly promoting biofilm formation of S. aureus Newman D2C in LB medium. This leads to another main influence on biofilm growth which is the medium used for the experiments.…”
mentioning
confidence: 86%
“…S. aureus infections can be recurred and costs for a long-term treatment along with productivity losses [12]. This recurrence is the result of biofilm formation and persistence inside body.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, biofilms can also act as source of spread for long term without being observed. Recent findings have shown that staphylococcal biofilm mechanisms are adaptable to the environmental changes and help the pathogen in adherence to the surfaces at any cost [12]. Genetic diversity could be one of the influencers among the biofilm production ability of this pathogen [16].…”
Section: Introductionmentioning
confidence: 99%